2006
DOI: 10.1128/jb.00630-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutator and Antimutator Effects of the Bacteriophage P1hotGene Product

Abstract: The Hot (homolog of theta) protein of bacteriophage P1 can substitute for the Escherichia coli DNA polymerase III subunit, as evidenced by its stabilizing effect on certain dnaQ mutants that carry an unstable polymerase III proofreading subunit (antimutator effect). Here, we show that Hot can also cause an increase in the mutability of various E. coli strains (mutator effect). The hot mutator effect differs from the one caused by the lack of . Experiments using chimeric /Hot proteins containing various domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Interestingly, at the same time it is capable of strongly increasing the mutability of another dnaQ mutant, dnaQ930 [13]. The precise reason for this mutator effect of Hot is unknown, but likely reflects a slightly different interaction of θ and Hot with ε that exacerbates the dnaQ930 defect (H98Y) [13,20]. This dual phenomenology permits a convenient test for expression of hot from the P1 prophage by checking whether these mutator/antimutator effects can be reproduced by a resident prophage.…”
Section: Expression Of Hot In P1 Lysogensmentioning
confidence: 98%
See 4 more Smart Citations
“…Interestingly, at the same time it is capable of strongly increasing the mutability of another dnaQ mutant, dnaQ930 [13]. The precise reason for this mutator effect of Hot is unknown, but likely reflects a slightly different interaction of θ and Hot with ε that exacerbates the dnaQ930 defect (H98Y) [13,20]. This dual phenomenology permits a convenient test for expression of hot from the P1 prophage by checking whether these mutator/antimutator effects can be reproduced by a resident prophage.…”
Section: Expression Of Hot In P1 Lysogensmentioning
confidence: 98%
“…Genetic studies have shown that hot, when cloned and expressed from the holE promoter on either a low-copy plasmid or the E. coli chromosome, is able to complement a ΔholE defect, reducing, for example, the ΔholE dnaQ49 mutator effect by some 1000-fold [9]. NMR structural studies on both θ and Hot revealed the two proteins to have near identical structures [10][11][12], further consistent with Hot being a fully functional homolog of θ. Alignment of the two proteins shows them to be approximately 48-53% identical (60-66% similar), which increases to 70 and 80%, respectively, when considering the structured core of the molecules [13].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations